PENETAPAN KADAR ASAM RETINOAT PADA KRIM MALAM YANG DI JUAL BEBAS DI KOTA PEKALONGAN DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Yusrilia Syafira (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2022)
Retinoic acid is one of the essential compounds added to night cream as it can remove dead skin cells, resulting in a white effect on the skin. However, it has a dangerous risk on the skin, which can cause inflammation, such as burning, stinging, redness, erythema, and hardening skin, and carcinogens if used for more than 6 months in a row. This study aimed to analyze the content of retinoic acid and determine its levels of retinoic acid. The samples selected were 10 night cream products circulating in Pekalongan City. This research was conducted qualitatively using thin layer chromatography with the mobile phase of n-hexane and 1% glacial acetic acid in ethanol (9:1). In the quantitative aspect, this study used UV-Vis spectrophotometry. The results obtained in thin layer chromatography obtained that the sample Rf value was the same as the standard Rf value of retinoic acid, which was 0.28, while the samples E, F, G, H, I, and J were 0.28. The UV-Vis spectrophotometry obtained retinoic acid levels that exceed the standard level from the National Food and Drug Agency (BPOM), which is 0.05%. The retinoic acid level of sample E was 0.08%, and sample F was 0.09%, respectively.